Regional Power Integration : Structural and Regulatory Challenges - World Bank (World Bank, 2012)
The Central America Regional Electricity Market (MER) trades electricity and transmission capacity among six Central American countries: Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua and Panama. The market differs from other electricity markets worldwide because it has its own regulatory body and system operator. Economic integration of the Central American countries has followed a natural evolution. The continuous increase in the demand for goods and services has been accompanied by political and institutional arrangements leading to the materialization of commercial and trade agreements aimed at benefiting the nationals of all the integrated nations at the lowest possible cost. This is particularly true in the electricity sector, which provides a key development service for the achievement of sustainable growth. In fact, electricity integration through cross-border power trade has been discussed by the Central American countries since the late 1970s. This report analyzes the progress of the Central American integrated electricity market, including the institutional, legal, regulatory and contractual framework of the MER and of each of the six national markets. It then identifies the main barriers that will have to be addressed in order to ensure a successful evolution to full operation of the Central American Electrical Interconnection System (SIEPAC) interconnection system and achieve true market integration.